Essays on applied microeconomics - Potter, Joel (Kansas State University, 2008)
This first essay empirically tests the Peltzman Effect utilizing a unique dataset that is used to investigate the behavior of Formula One race car drivers. The race-level dataset was culled from various sources and includes detailed information from a total of 547 Formula One races. A fixed effects model is used to determine whether or not Formula One race car drivers alter their behavior in response to changes in the conditional probability of a casualty given an accident. The empirical estimates support economic theory; Formula One race car drivers become more reckless as their cars become safer, ceteris paribus. Furthermore, the behavioral response of drivers is larger when the analysis is confined to changes in the conditional probability of a fatality given an accident. The second essay utilizes data from the National Youth Survey to reevaluate key conclusions from Fair (1978). This study supports some of Fair's empirical findings; however, the estimates obtained from this research contradict Fair in several key ways. For example, this paper finds that the coefficients of occupation and education are both statistically significant but the signs are opposite to those in Fair (1978). An even more noteworthy contradiction is the negative relationship between years of marriage and infidelity; this suggests that marriage longevity is positively related to that of match quality of the relationship. Also included in these new specifications are independent variables that better control for individual heterogeneity, factors such as general health, race, and alcohol consumption. This essay presents a simple model to characterize the outcome of a land dispute between two rival parties using a Stackelberg game. This study assumes that opposing parties have access to different technologies for challenging and defending in conflict. Conditions are derived under which territorial conflict between the two parties is less likely to persist indefinitely. Allowing for an exogenous destruction term as in Garfinkel and Skaperdas (2000), it is shown that, when the nature of conflict becomes more destructive, the likelihood of a peaceful outcome, in which the territory's initial possessor deters the challenging party, increases if the initial possessor holds more intrinsic value for the disputed land.
Keywords: safety; cheating; regulation; conflict; contest; Economics, General (0501)